2017
DOI: 10.1021/jacs.7b07603
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 Substrates Identified by Genetically Encoded Active Site Photocrosslinking

Abstract: The histone deacetylase family comprises 18 enzymes that catalyze deacetylation of acetylated lysine residues, however, the specificity and substrate profile of each enzyme remains largely unknown. Due to transient enzyme-substrate interactions, conventional co-immunoprecipitation methods frequently fail to identify enzyme-specific substrates. Additionally, compensatory mechanisms often limit the ability of knockdown or chemical inhibition studies to achieve significant fold-changes observed by acetylation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Indeed, one report with KDAC8 indicated that the authors were able to validate only approximately 30% of the cross‐linked proteins as substrates by in vitro methods. Additionally, their approach did not identify a known substrate of KDAC8, SMC3 89 . Thus, this type of experiment can be useful for identifying potential substrate leads for further study, and perhaps strengthening evidence for suspected enzyme‐substrate pairs that have previously been identified by other means.…”
Section: Approaches For Kdac Substrate Identificationmentioning
confidence: 98%
See 4 more Smart Citations
“…Indeed, one report with KDAC8 indicated that the authors were able to validate only approximately 30% of the cross‐linked proteins as substrates by in vitro methods. Additionally, their approach did not identify a known substrate of KDAC8, SMC3 89 . Thus, this type of experiment can be useful for identifying potential substrate leads for further study, and perhaps strengthening evidence for suspected enzyme‐substrate pairs that have previously been identified by other means.…”
Section: Approaches For Kdac Substrate Identificationmentioning
confidence: 98%
“…In this way, the catalytic efficiency of a particular KDAC for different acetylation sites can be compared 83,88 . Most in vitro studies screen several acetylated peptides, which correspond to partial sequences of acetylated proteins, as substrates 83,88‐91 . In other reports, individual peptides corresponding to a particular protein of interest or known substrate were shown to be deacetylated 74,92‐94 .…”
Section: Approaches For Kdac Substrate Identificationmentioning
confidence: 99%
See 3 more Smart Citations